2016
DOI: 10.1063/1.4953905
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the cooperative exciton dissociation process based on dimensional and hot charge-transfer state effects in an organic photocell

Abstract: This paper discusses the exciton dissociation process at the donor-acceptor interface in organic photocells. In our previous study, we introduced a local temperature to handle the hot chargetransfer (CT) state and calculated the exciton dissociation probability based on the 1D organic semiconductor model [T. Shimazaki and T. Nakajima, Phys. Chem. Chem. Phys. 17, 12538 (2015)]. Although the hot CT state plays an essential role in exciton dissociations, the probabilities calculated are not high enough to efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Overall, the low-frequency phonons may play central roles in the OPV operations at room temperature because such disorder motions in the polymers and also in the PC 61 BM fullerene clusters may enhance the density of the states for the separated electron−hole pairs coupled with the dense phonon bath, contributing to the efficient photocurrents. 21…”
Section: Electron−hole Dissociation After Photoinduced Charge Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the low-frequency phonons may play central roles in the OPV operations at room temperature because such disorder motions in the polymers and also in the PC 61 BM fullerene clusters may enhance the density of the states for the separated electron−hole pairs coupled with the dense phonon bath, contributing to the efficient photocurrents. 21…”
Section: Electron−hole Dissociation After Photoinduced Charge Separationmentioning
confidence: 99%
“…This meant that the Coulomb binding potentials are overcome by the entropy, as represented in Figure B bottom. The above two different mechanisms (hot exciton mechanism vs entropy mechanism) have been in strong discussions in current researches by experiments and by theoretical approaches. , As mentioned above, the connection among the nuclear motions, the electronic coupling and geometries in Figure B is required to be clarified to further understand the charge generation mechanism by the entropy. This entropy role is thus definitely distinguished from the conventional exciton model in Figure B.…”
Section: Dynamic Excitonmentioning
confidence: 99%
See 1 more Smart Citation
“…The CT mechanisms have gone through heated discussions in the past several years. Notably, some reports have emphasized the importance of hot CT states, that is, excess energy in the promotion of charge separation. , While other works combined with experimental and theoretical data suggest that the direct excitations are also important in promoting charge separation. ,,, Normally, direct excitations have not been considered for P3HT / PC 61 BM because of the weak absorption of PC 61 BM and small f of CT states. However, it is different for P3HT /nonfullerene systems owing to larger f of their CT states presented in Figures and S4–S6.…”
Section: Resultsmentioning
confidence: 99%
“…The LUMO energy difference (offset) between the donor and acceptor materials plays an essential role in the dissociation of such strongly bound excitons. [2][3][4][5][6][7][8][9] The energy offset at the donoracceptor junction can give excess energy to the exciton and assist the dissociation process required to generate a free electron and a hole. 8,9 Several experiments have demonstrated that the energy conversion efficiency of an organic photocell device is suppressed in small offset cases.…”
Section: Introductionmentioning
confidence: 99%